2021
DOI: 10.1097/grf.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Uterus Transplantation: A 50-Year Journey

Abstract: This paper provides an analysis of the last 50 years of uterus transplantation (UTx). Animal research on UTx began in the 1960s, aiming to solve tubal factor infertility. The success of in vitro fertilization shifted the focus onto uterine factor infertility. Early research in small and large animals improved following the advent of immunosuppression and established the uterus' ability to tolerate cold ischemia and to function following vessel reanastamosis. Upon the achievement of the first live birth followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In the wake of the world's first successful live birth in 2014, 1 uterus transplantation has rapidly expanded throughout the world, with 34 transplants and 22 live births in the United States alone. 2,3 For all of its success, however, pregnancy after a uterus transplant remains complex, and pregnancy complications such as pre-eclampsia (PE) have been reported. Initial single center reports 2,4,5 suggested that PE was observed in 8-17.6% of patients, and this high rate of PE has largely been attributed to immunosuppression given the increased prevalence of PE in solid organ transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wake of the world's first successful live birth in 2014, 1 uterus transplantation has rapidly expanded throughout the world, with 34 transplants and 22 live births in the United States alone. 2,3 For all of its success, however, pregnancy after a uterus transplant remains complex, and pregnancy complications such as pre-eclampsia (PE) have been reported. Initial single center reports 2,4,5 suggested that PE was observed in 8-17.6% of patients, and this high rate of PE has largely been attributed to immunosuppression given the increased prevalence of PE in solid organ transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Uterus transplantation has emerged as a highly effective treatment option for uterine factor infertility (UFI). In the wake of the world's first successful live birth in 2014, 1 uterus transplantation has rapidly expanded throughout the world, with 34 transplants and 22 live births in the United States alone 2,3 . For all of its success, however, pregnancy after a uterus transplant remains complex, and pregnancy complications such as pre‐eclampsia (PE) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the number of UTx recipients is increasing. 1 , 2 , 3 Many recipients have Mayer-Rokitansky-Kuster-Hauser syndrome, which may include unilateral kidney agenesis in addition to a congenitally absent uterus and vaginal aplasia. 4 Therefore, kidney dysfunction is a potential complication of UTx.…”
Section: Introductionmentioning
confidence: 99%